Increasing gastric juice pH level prior to anti-Helicobacter pylori therapy may be beneficial to the healing of duodenal ulcers - FAN, HONG-YUN (D.A. Spandidos, 2013)
The aim of this study was to observe the efficacy of clarithromycin-based triple therapy for Helicobacter pylori (Hp)-infected duodenal ulcer when combined with different pH levels of gastric juices. A total of 160 patients with Hp-infected duodenal ulcers were randomly allocated into two groups. Patients in the treatment group (n=80) were administered a 20-mg dose of omeprazole twice daily for 1 week and then the treatment and control groups (n=80) received therapy for Hp infection and duodenal ulcers. We observed the ulcer healing stage, the content of anti-Hp IgA in gastric juice and the Hp eradication rate before and after proton pump inhibitor therapy in the two groups. Results revealed that the Hp eradication rate in the treatment group was 93% compared with 81% in the control group, and the difference was statistically significant (P<0.05). The ulcer healing rate in the treatment group was 93%, compared with 70% in the control group (P<0.05). A positive linear correlation was observed between gastric pH and the content of anti-Hp IgA in gastric juice (P<0.05). Increasing gastric pH prior to anti-Hp therapy may be beneficial to the eradication of Hp and for promoting the healing of duodenal ulcers.